Grasping the Legal and Bioethical Issues of “Wrongful life” - Κουδουμά (Ioulia Koudouma), Ιουλία (Bioethica, 2018)
The present manuscript focuses on the special features of “wrongful life” cases and the ethical philosophical questions they arise. Our main goal is to conclude whether the handicapped child should be compensated by the doctor who negligently failed to diagnose or inform the child’s parents about potential birth defects. Is the doctor morally responsible? Should he be held liable for the existence of the impaired child? Can a life ever be considered a source of damage? Is handicapped life of less value? Through the analysis of moral and legal theories as well as the comparative overview of the international- basically European and Greek case law we find out that the moral evaluation of the doctor’s behavior is in coincidence with the general practice of courts to dismiss wrongful life lawsuits. Contrary to the argument for recognizing wrongful life actions based on the lack of social support structures for the vulnerable and retarded children, we conclude that their financial support is a matter of social policy and it should not be passed on the doctor who did not cause the impaired condition.